JIRA 5.2 essentials : learn how to track bugs and issues, and manage your software development projects with JIRA - Li, Patrick (Professional expertise distilled, 2013)
Learn how to track bugs and issues, and manage your software development projects with JIRA Learn how to set up JIRA for software development Effectively manage and handle software bugs and issues Includes updated JIRA content as well as coverage of the popular GreenHopper plugin In Detail Atlassian's JIRA provides issue tracking and project tracking for software development teams to aid speed of development and quality of code. This book will show you how to develop software more efficiently by planning, designing, and customizing your own JIRA implementation. JIRA is a popular issue tracking product designed for better bug tracking, issue tracking, and project management. JIRA 5.2 Essentials provides a comprehensive guide covering everything you will need to plan, set up, design, customize, and manage your software development projects efficiently and to a professional standard. In this practical book you will learn how to design and implement JIRA for project and issue tracking. You will jump into the installation and design of JIRA before going through the required techniques to effectively manage issues that threaten your software development project. Each chapter builds on the last, taking you through important concepts and techniques such as business processes and workflows, setting up e-mail notifications, field and screen management, and reporting. Using these techniques you will be able to make JIRA adapt to your organization and save time and energy by developing software more efficiently. Newly improved and updated to JIRA 5.2 this book also includes a section about GreenHopper and Agile development with JIRA.